Avaliação da qualidade do ar em interiores e ambientes abertos de uma universidade em São Carlos - SP - Comin, Tatiane Tagino (2016)
Research in the area of indoor air quality (IAQ) has increased in recent decades, but IAQ standards remain scarce in Brazil and are only applicable to air-conditioned environments. Classrooms have attracted particular research attention because high occupancy rates associated with inadequate building maintenance and low ventilation rates contribute to poor air quality, affecting the health of teachers and students. It is therefore necessary to monitor total particulate matter (TPM), the respirable particulate fractions (PM2.5 and PM10), carbon dioxide (CO2), carbon monoxide (CO), and volatile organic compounds (VOCs) in order to avoid adverse impacts. The objective of the present research was to determine the indoor concentrations of these species in two air-conditioned and two naturally ventilated classrooms at the Federal University of São Carlos (UFSCar), as well as in the adjacent outdoor atmosphere, providing data for comparison of these locations and evaluation of compliance with existing legislation concerning concentrations in open and closed environments. UFSCar is located on the Washington Luís highway, which carries intense vehicular traffic, and is close to two chemical plants, one producing paints and solvents and the other manufacturing paper and packaging, whose emissions of particulate matter and gases affect local air quality. Additional parameters determined were air temperature, relative humidity, noise, and rates of occupancy and ventilation of rooms. The particulates collected were submitted to chemical characterization using Inductively Coupled Plasma Mass Spectrometry (ICP-MS) and Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). The results showed that in the case of the air-conditioned rooms, levels of noise and CO2 were unsatisfactory, according to the existing regulations, and the same was found for temperature, occupancy rate, and noise in the rooms with natural ventilation. Chemical analysis of the particulates identified 27 elements (Al, Au, Ba, Ca, Cd, Ce, Cu, Fe, Ga, K, La, Mg, Mn, Na, Ni, Pb, Pr, Rb, S, Sb, Sn , Sr, Ti, V, Y, Zn, and Zr). Possible origins of these elements included external sources such as vehicle emissions, soil dust resuspension, and sugarcane burning, as well as internal sources such as the chalk (which contains calcium compounds) used by teachers. Measurements of ventilation rates revealed the importance of changes of air in the indoor environment for reducing CO2 concentrations. Overall, it could be concluded that particulate concentrations were higher in the naturally ventilated rooms and that for most of the parameters (in both types of room), levels were higher in the internal environments, compared to the outdoor atmosphere (I/O ratio >1.0).